Sodium Glucose Cotransporter-2 Inhibitors: Spotlight on Favorable Effects on Clinical Outcomes beyond Diabetes - Čertíková Chábová, Věra; Zakiyanov, Oskar (International journal of molecular sciences, 2022)
Sodium glucose transporter type 2 (SGLT2) molecules are found in proximal tubules of the kidney, and perhaps in the brain or intestine, but rarely in any other tissue. However, their inhibitors, intended to improve diabetes compensation, have many more beneficial effects. They improve kidney and cardiovascular outcomes and decrease mortality. These benefits are not limited to diabetics but were also found in non-diabetic individuals. The pathophysiological pathways underlying the treatment success have been investigated in both clinical and experimental studies. There have been numerous excellent reviews, but these were mostly restricted to limited aspects of the knowledge. The aim of this review is to summarize the known experimental and clinical evidence of SGLT2 inhibitors' effects on individual organs (kidney, heart, liver, etc.), as well as the systemic changes that lead to an improvement in clinical outcomes.
Keywords: heart failure; kardiovaskulární systém; Sodium; chronic kidney disease; Glucose; sodík; Humans; diabetes; glukosa; Cardiovascular System; glifloziny; Diabetes Mellitus, Type 2; SGLT2 inhibitors; transportér 2 pro sodík a glukózu; Sodium-Glucose Transporter 2 Inhibitors; SGLT2; lidé; diabetes mellitus 2. typu; Sodium-Glucose Transporter 2